Peningkatan Prestasi Belajar Matematika melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Divisions) pada Siswa Kelas VII.C SMPN 3 Masbagik Semester II - Yam, Yam (Lembaga Yasin AlSys, 2021)
This Classroom Action Research was conducted by applying the STAD type cooperative learning model (Student Teams Achievement Divisions) in order to improve the quality of the learning process and is a concept of learning activities that assist teachers in carrying out Mathematics learning activities taught by trying to maximize the active role of students, especially their knowledge. and how to apply it in everyday life. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of student activities working and experiencing, not transferring knowledge from teacher to student. The quality of learning is more important than the results. This Classroom Action Research (CAR) was conducted with the aim of knowing the improvement of mathematics learning achievement through the application of the STAD Type Cooperative learning model (Student Teams Achievement Divisions) in class VII-C students of SMPN 3 Masbagik in the 2020/2021 school year. This Classroom Action Research (CAR) was carried out in stages 2 cycles, and from the results of the actions that have been carried out it has been proven to improve student learning achievement both in terms of classical student learning completeness, namely in the first cycle of 72%, it can increase to 92% in the second cycle. it means that there is an increase of 20% and in terms of the average value of the evaluation results, namely in the first cycle of 72 to 87 in the second cycle, this means that there is an increase of 15. In terms of student activity in this classroom action research also shows an increase in the level of learning activity students from the Moderately Active category in cycle I became the Active category, meaning there was an increase as well.